Energy flexible CHP-DHN systems: Unlocking the flexibility in a real plant - A. Mugnini; G. Comodi; D. Salvi; A. Arteconi (Energy Conversion and Management: X, 2021)
The purpose of this paper is to identify and analyze the impact of flexibility enablers in cogeneration and district heating network (CHP-DHN) plants by means of a real case study located in central Italy. A wider definition of energy flexibility applicable to the entire energy supply chain (i.e. production, transport and usage) is used in this analysis. In particular the flexibility is intended as the capability of each part of the system to produce a variation in its load curve, while ensuring the required performance. In this sense energy efficiency technologies, the use of energy storage and advanced control techniques can be seen as flexibility enablers potentially available in each section of the energy system.The innovative contribution of this work is to propose flexibility strategies in compliance with the constraints imposed by both the managers and users. The study aims to show possible ways to activate flexibility services to be used with known instruments and to quantify their impact with a simulation-based approach. In particular, three different flexibility instruments are identified in different sections of the plant: (i) the use of a thermal energy storage (TES) in the generation side, (ii) the optimal management of the DHN supply temperature (energy distribution side) and (iii) the management of the thermostatically controlled loads (TCLs) of the final users (demand side) connected to the network. Through the implementation of simulation models calibrated with available measurements, the influence of these flexibility instruments on the energy/environmental performance is evaluated in comparison to the current configuration of the plant. Results confirm the great impact of the TES to increase the CHP working hours and, as a consequence, a primary energy saving increase is obtained in mid-season and in summer season. Whereas the optimal management of the water supply temperature in the DHN allows to obtain 1% fuel reduction in a typical winter week and 2% in a typical summer week. As far as the activation of the demand side flexibility is concerned, the effect of the management of TCLs on energy conservation is demonstrated: 1 °C reduction of the setpoint of all the residential users during a typical winter day produces a 7.3% reduction of the DHN thermal demand. However, its impact on the generation side (i.e. to reduce the electricity/thermal production of the CHP at specific times) is limited due to the characteristics of the considered CHP plant (the CHP engine is sized to cover only the thermal baseload and it scarcely affected by thermal demand variations). The analysis proposed helps to obtain valuable hints on unlocking the energy flexibility in CHP-DHN plants useful for a better management of such systems.